The Three Phase Induction Motor Test Using MATLAB 2021b/SIMULINK at Bukit Energi Servis Terpadu, Ltd - Destra Andika Pratama; Masayu Anisah; Kabul Andi Setiyadi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The purpose of the paper is to investigate the performance characteristics squirrel-cage induction motor available. This paper discusses determination parameters for three-phase induction motor based on experimental data, which the standard test data is not completely available in the end-users. Alternatively, equivalent circuit parameters should be estimated based on the released performance data of the induction motor. This paper also describes MATLAB 2021b/Simulink implementation of three phases of induction motor testing, which includes the no-load, full load, and locked rotor tests were performed to identify the equivalent circuit parameters. The value calculated of parameters simulation results has been compared to experimental values as verification and validation techniques. The deviation of measured values was diagnosed between 0.13% and 1.31%.